Electrocatalytic reduction of low concentration CO2. Issue 6 (28th November 2018) - Kumagai, Hiromu; Nishikawa, Tetsuya; Koizumi, Hiroki; Yatsu, Taiki; Sahara, Go; Yamazaki, Yasuomi; Tamaki, Yusuke; Ishitani, Osamu
Abstract : Electrocatalytic reduction of low concentration CO2 was selectively and efficiently carried out by using a Re(I) complex with high CO2 -capturing ability. Abstract : Utilization of low concentration CO2 contained in the exhaust gases from various industries and thermal power stations without the need for energy-consuming concentration processes should be an important technology for solving global warming and the shortage of fossil resources. Here we report the direct electrocatalytic reduction of low concentration CO2 by a Re(i )-complex catalyst that possesses CO2 -capturing ability in the presence of triethanolamine. The reaction rate and faradaic efficiency of CO2 reduction were almost the same when using Ar gas containing 10% CO2 or when using pure CO2 gas, and the selectivity of CO formation was very high (98% at 10% CO2 ). At a concentration of 1% CO2, the Re(i ) complex still behaved as a good electrocatalyst; 94% selectivity of CO formation and 85% faradaic efficiency were achieved, and the rate of CO formation was 67% compared to that when using pure CO2 gas. The electrocatalysis was due to the efficient insertion of CO2 into the Re(i )–O bond in fac -[Re(dmb)(CO)3 OC2 H4 N(C2 H4 OH)2 ] (dmb = 4, 4′-dimethyl-2, 2′-bipyridine).